Pengaruh Penduduk Usia Muda dan Tingkat Pendidikan Tinggi Terhadap Tingkat Pengangguran di Indonesia - Rafiq Affandi; Novya Zulva Riani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Unemployment is one of the most crucial labor market issues in Indonesia, particularly among young people and higher education graduates. This study aims to analyze the effects of the proportion of young population, higher education attainment, and technological skills on the unemployment rate in Indonesia, while considering minimum wages, labor force participation rate (LFPR), and economic growth as control variables. The method employed is panel data regression with a fixed effect model, based on secondary data from 34 provinces in Indonesia over the period 2018–2024. The results indicate that the young population, higher education attainment, and technological skills have a positive and significant effect on the unemployment rate. Conversely, minimum wages, LFPR, and economic growth have a negative and significant effect on unemployment. These findings suggest that the increasing number of young people and participation in higher education have not been matched by labor market readiness. Therefore, more responsive policies are needed to align education and job training with industry demands in order to reduce unemployment rates.